A SERIAL OF BURN INJURY CASES FROM MARINE ACCIDENT OF LOCAL PASSENGER FERRY “CANTIKA EXPRESS 77” IN EAST NUSA TENGGARA, INDONESIA - Robertus Arian Datusanantyo; Angela Djunaedi (Universitas Airlangga, 2026)
Highlights: This Hospitals near active local boat transport areas should anticipate risks such as hypothermia, inhalation injury, and extensive full-thickness burns in maritime burn victims. Elderly populations require tailored evacuation strategies due to slower response times during emergencies. Strengthening safety protocols and implementing fire safety education have been proven effective in improving preparedness to reduce the risk of fire-related accidents and burn injuries in local transportation. Abstract: Introduction: Despite marked decrease in total maritime accidents in Indonesia from 2022-2023, there was increase in total number of fire-related maritime accidents. This highlighted the awareness about fire safety protocols in local waterway transportation and brings lessons to related sectors including referral hospital. We present our experience regarding burn injury cases caused by fire accident of local transport boat. Case Illustration: There were five burn inpatients among hundreds of victims who were sent to our hospital after the fire accident of local transport boat. One case was lethal with the highest total burn surface area (TBSA) of 42% full-thickness to superficial dermal burn and inhalation trauma. Skin grafting was performed in one patient. The lowest TBSA was 7.5% with mixed dermal burn. Discussion: Thoracolumbar is the most affected site with full-thickness burn despite no affected thoracoabdominal site, reflecting the act of running away from the fire source. We also observed hypothermia caused by abandoning boat to the open water in all inpatients. Emergency response demo was not performed by the crew and the accident was worsened by fire extinguisher malfunction and passenger overcapacity. Conclusion: To lower the risk of accidents and injury, awareness and obedience of safety protocols should be emphasized. Hospital in area with extensive local transport boat operating should prioritize burn treatment management strategy including inhalation trauma, hypothermia, and extensive full-thickness burns.